Genomic species identification of acinetobacter of clinical isolates by 16S rDNA sequencing - Misbah, S.; Hassan, H.; Yusof, M.Y.; Hanifah, Y.A.; AbuBakar, Sazaly (2005)
Introduction: This study aims to identify Acinetobacter of clinical isolates from the University of Malaya Medical Centre (UMMC),Kuala Lumpur, to the species level by 16S rDNA sequencing. Methods: 12 representative Acinetobacter isolates of the UMMC inpatients were randomly picked and used for the study. The 16S rDNA sequences were determined and phylogenetic relationships to all known Acinetobacter species were established. Results: Based on the 16S rDNA sequences, all the UMMC isolates were identified as Acinetobacter baumannii. The isolates shared a common ancestral lineage with the prototypes Acinetobacter baumannii DSM30007 and DSM30008 with 99-100 percent sequence similarities. The isolates could be differentiated into two groups by a single nucleotide difference(thymine-cytosine) within the 16S rRNA sequence.Three different genotypes, 1, 3 and 4, were recognised using REP-PCR. The previously uncharacterised Acinetobacter isolates from the UMMC were identified by their 16S rDNA sequences as Acinetobacter baumannii. The isolates were distinguished into at least three different genotypes by REP-PCR genotyping. These findings confirmed for the first time the presence of Acinetobacter baumannii of different genotypes among patients at UMMC.